2004
DOI: 10.1016/j.bse.2004.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics and condensed tannins in relation to altitude in neotropical Pteridium spp

Abstract: Two species of neotropical bracken, Pteridium caudatum (L.) Maxon (P.c.) and P. arachnoideum (Kaulf.) (P.a.), thrive dominantly in habitats extending from near the sea level to the Andean alpine zone around 3000 m altitude. The scope of sources of stress associated with elevation has three main components: plant competition for resources, activity of herbivores/pathogens, and climate. The contribution of each component varies greatly from place to place and bracken must respond with considerable physiological/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…We had observed earlier that a direct correlation exists between total phenolics accumulation in aerial parts of P. arachnoideum and frond ontogeny (Alonso-Amelot et al, 2004). Although this might imply a reduced chemical defense at the fragile young stage of the frond, other compensatory mechanisms are present in the growing blade to protect it.…”
Section: Phenolics Content and Relative Position Of Pinnae Along The mentioning
confidence: 87%
See 2 more Smart Citations
“…We had observed earlier that a direct correlation exists between total phenolics accumulation in aerial parts of P. arachnoideum and frond ontogeny (Alonso-Amelot et al, 2004). Although this might imply a reduced chemical defense at the fragile young stage of the frond, other compensatory mechanisms are present in the growing blade to protect it.…”
Section: Phenolics Content and Relative Position Of Pinnae Along The mentioning
confidence: 87%
“…Volatile solvents were removed from each fraction and their volume was corrected to 100.0 ml. Aliquots (1 ml) were destined for analysis using the reported method (Alonso-Amelot et al, 2004) and employing Sephadex LH-20-purified quebracho (Schinopsis quebracho-colorado (Schltdl.) F.A.…”
Section: Extraction and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Positive relationships with altitude were observed in Andean alpine species of Dennstaedtiaceae, Pteridium caudatum (L.) Maxon and Pteridium arachnoideum (Kaulf.) Maxon (Alonso-Amelot et al 2004, as well as a species of Jungermanniaceae, Jungermannia exsertifolia Steph. subsp.…”
Section: Phenolic Content and Profilementioning
confidence: 99%
“…A recent comparative analysis of the chemistry of the two bracken species (Alonso-Amelot et al 2004) revealed important differences in content of condensed tannins in the fronds. Concentration in P. arachnoideum is nearly three times that of P. caudatum, suggesting a possible phytochemical base for the preference of B. palliata for the fi rst of the two species.…”
mentioning
confidence: 99%